2009
DOI: 10.1002/chem.200900914
|View full text |Cite
|
Sign up to set email alerts
|

One‐Step Synthesis of Folic Acid Protected Gold Nanoparticles and Their Receptor‐Mediated Intracellular Uptake

Abstract: We report here a facile method to obtain folic acid (FA)-protected gold nanoparticles (Au NPs) by heating an aqueous solution of HAuCl(4)/FA in which FA acts as both the reducing and stabilizing agent. The successful formation of FA-protected Au NPs is demonstrated by UV/Vis spectroscopy, transmission electron microscopy (TEM), selected-area electron diffraction (SAED), X-ray photoelectron spectroscopy (XPS), and Fourier transform infrared spectroscopy (FTIR). The intracellular uptake of these nanoparticles is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 43 publications
5
51
0
Order By: Relevance
“…In this paper, an innovative technique has been developed by using MNP-Fe 3 O 4 under ELMF exposure to generated localized physical cell damage and eventually kills tumor cells. Comprehensive studies have reported the biological effects of external static or alterable magnetic field in the last decades313233343536373839. However, the specific mechanism of ELMF on biological system has not yet been fully investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, an innovative technique has been developed by using MNP-Fe 3 O 4 under ELMF exposure to generated localized physical cell damage and eventually kills tumor cells. Comprehensive studies have reported the biological effects of external static or alterable magnetic field in the last decades313233343536373839. However, the specific mechanism of ELMF on biological system has not yet been fully investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Folate-functionalized gold nanoparticles are selectively internalized into cells expressing folate receptor, a process which is significantly inhibited by excess free folic acid (Li et al 2009). Several studies have employed folate as a targeting ligand for gold nanoparticles loaded with a chemotherapeutic cargo (Prabaharan et al 2009; Asadishad et al 2010; Patra et al 2010; Manju and Sreenivasan 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, we would better come to the conclusion that MNP-Fe 3 O 4 did not a®ect important functions (such as chromosome function), but the mechanism of particles entering into the cell is not yet very clear. 35,36 During this experiment, cultured cells were divided into nine parts, including three control groups and six experiment groups. In control groups 1 and 2, the cells were only under LFAMF irradiation during 120 min.…”
Section: Discussionmentioning
confidence: 99%